Eportfolios: From description to analysis - Brandes, Gabriella Minnes; Boskic, Natasha (International Review of Research in Open and Distributed Learning, 2008)
In recent years, different professional and academic settings have been increasingly utilizing ePortfolios to serve multiple purposes from recruitment to evaluation. This p aper analyzes ePortfolios created by graduate students at a Canadian university. Demonstrated is how students’ constructions can, and should, be more than a simple compilation of artifacts. Examined is an online learning environment whereby we shared knowledge, supported one another in knowledge construction, developed collective expertise, and engaged in progressive discourse. In our analysis of the portfolios, we focused on reflection and deepening understanding of learning. We discussed students’ use of metaphors and hypertexts as means of making cognitive connections. We found that when students understood technological tools and how to use them to substantiate their thinking processes and to engage the readers/ viewers, their ePortfolios were richer and more complex in their illustrations of learning. With more experience and further analysis of exemplars of existing portfolios, students became more nuanced in their organization of their ePortfolios, reflecting the messages they conveyed. Metaphors and hypertexts became useful vehicles to move away from linearity and chronology to new organizational modes that better illustrated students’ cognitive processes. In such a community of inquiry, developed within an online learning space, the instructor and peers had an important role in enhancing reflection through scaffolding. We conclude the paper with a call to explore the interactions between viewer/ reader and the materials presented in portfolios as part of learning occasions.